"Accidental Nations, " "Nations in the Making": James Bryce's Colonialist Interpretation of Latin American Nations. (2nd January 2020) - Alonso, Ricardo Ledesma
Abstract : The political and historiographical discourses of the British intellectual and traveler James Bryce (1838–1922) have been characterized as representative of the late-Victorian liberal thought. Following this interpretative framework, scholarship has focused on the analysis of the key principles of Bryce's liberal ideology, such as "self-government", "democracy" and "international law." This article examines a scarcely discussed aspect of the Brycean discourses: their colonialist imprint, which is particularly evident in Bryce's historical-political interpretations of Latin American nations. This article contends that in his work South America: Observations and Impressions (1912), Bryce built a scientific discourse, a knowledge that, framed in late-Victorian British liberal nationalism and imperial liberalism, inferiorized and discredited Latin American nations and justified the economic and cultural dominance that the European civilization, and in particular, the British Empire, exercised over them.